DPP and DSP are Necessary for Maintaining TGF-β1 Activity in Dentin. (July 2014) - Yamakoshi, Y.; Kinoshita, S.; Izuhara, L.; Karakida, T.; Fukae, M.; Oida, S.
Porcine dentin sialophosphoprotein (DSPP) is the most abundant non-collagenous protein in dentin. It is processed by proteases into 3 independent proteins: dentin sialoprotein (DSP), dentin glycoprotein (DGP), and dentin phosphoprotein (DPP). We fractionated DPP and DSP along with TGF-β activity by ion exchange (IE) chromatography from developing pig molars and measured their alkaline phosphatase (ALP)-stimulating activity in human periodontal (HPDL) cells with or without TGF-β receptor inhibitor. We then purified TGF-β-unbound or -bound DPP and DSP by reverse-phase high-performance liquid chromatography (RP-HPLC) using the ALP-HPDL system. The TGF-β isoform bound to DPP and DSP was identified as being TGF-β1 by both ELISA and LC-MS/MS analysis. We incubated carrier-free human recombinant TGF-β1 (CF-hTGF-β1) with TGF-β-unbound DPP or DSP and characterized the binding on IE-HPLC using the ALP-HPDL system. When only CF-hTGF-β1 was incubated, approximately 3.6% of the ALP-stimulating activity remained. DPP and DSP rescued the loss of TGF-β1 activity. Approximately 19% and 10% of the ALP stimulating activities were retained by the binding of TGF-β to DPP and DSP, respectively. The type I collagen infrequently bound to CF-hTGF-β1. We conclude that both DPP and DSP help retain TGF-β1 activity in porcine dentin.